Highly localized distributed Brillouin scattering response in a photonic integrated circuit - Zarifi, Atiyeh; Stiller, Birgit; Merklein, Moritz; Li, Neuton; Vu, Khu; Choi, Duk-Yong; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (APL Photonics, 2018)
The interaction of optical and acoustic waves via stimulated Brillouin scattering (SBS) has recently reached on-chip platforms, which has opened new fields of applications ranging from integrated microwave photonics and on-chip narrow-linewidth lasers, to phonon-based optical delay and signal processing schemes. Since SBS is an effect that scales exponentially with interaction length, on-chip implementation on a short length scale is challenging, requiring carefully designed waveguides with optimized opto-acoustic overlap. In this work, we use the principle of Brillouin optical correlation domain analysis to locally measure the SBS spectrum with high spatial resolution of 800 μm and perform a distributed measurement of the Brillouin spectrum along a spiral waveguide in a photonic integrated circuit. This approach gives access to local opto-acoustic properties of the waveguides, including the Brillouin frequency shift and linewidth, essential information for the further development of high quality photonic-phononic waveguides for SBS applications.
CRIS-Team Scopus Importer:2021-06-29